'The triangle that moves the mountain': evaluation of road safety intervention model in Phuket, Thailand. (7th October 2012) - Seetamanotch, W
Abstract : Background: Road traffic accident mortality rate in Phuket was very high. In 2006, it was the third highest in Thailand. Aims/Objectives/Purpose: To evaluate the impact of road safety intervention programmes in Phuket. Methods: Road traffic accident mortality has been monitored in all Phuket's hospitals since 1997. In 2008, lack of solution of the problem prompted the development of a new model that can address the complex challenges arising from social development. There are three key elements in this model: (1) creation of relevant knowledge through research (2) social movement and (3) Political involvement. Providing the key evidence for example, number of injury cases in black spots, risk behaviours, and the evidence-based solutions in other countries to key stakeholders from various sectors and disciplines during regular meetings was essential to mobilise the social movement. The identified risks factors were corrected by the participants themselves or by advocated to the local authorities. Results/Outcomes: Since 2008, there were 26 meetings among the key stakeholders for example, police, transportation authority and public health officer. Outcomes of the meeting included improvement of 20 black spots, three local regulations and helmet enforcement campaign. The average number of fatalities reduced 29% (192 to 136) Significance/Contribution to the Field: This leverage model is effective and practical to solve the complex, interconnected and challenging problem such as traffic injury especially in the low and middle income countries.